Efforts to Improve the Batik Design Capability of the Babussalam Islamic Boarding School Jombang in the Middle of a Pandemic - Kusuma Wardhani Mas’udah; Nur Aini Fauziyah; Euis Nurul Hidayah; Syahrul Munir (Nusantara Science and Technology Proceedings, 2021)
Islamic Boarding School throughout the history of the development of Indonesian society has played an important role, especially in the development of religious education. Currently, there is a phenomenon of the transformation of the role of Islamic Boarding School which focuses on the balance between religious knowledge and science. However, so far, capacity-building activities during the Covid-19 pandemic are considered ineffective. The batik design training program using CorelDraw software is implemented as a form of the OPOP program for the development of an Islamic Boarding School-based economy. The method of implementing this activity is by conducting training, implementation, mentoring, and networking. From the results of the field evaluation, the economic activities of the pesantren have received a very positive response from the students.